Ion energy distributions in RF sheaths with dust particles - Kravchenko, O. Yu.; Yastrub, Yu. A.; Levada, G.I.; Lisitchenko, T.Y. (Вопросы атомной науки и техники, 2009)
We study ion energy distributions functions (IEDFs) within an rf sheath with dust particles in SiH₄ radio-frequency discharges and compare results with ones in Ar rf discharges. The simulations are carried by PIC/MCC method over a wide range of pressure, dust density and dust radius. Our model includes electron-neutral collisions, various kinds of collisions of ions with neutrals, positive-negative ion collisions. Results of calculations show that IEDFs for positive ions SiH⁺³ in silane rf-discharge essentially differ from IEDFS for positive ions in Ar discharges. Ions near electrodes get greater energy in electronegative discharge in consequence of inessential charge exchange processes in the rfsheath. Peaks of high energy ions are appeared in IEDFs, which are caused by significant decreasing of the radiofrequency sheath width and the ratio of ion penetrating time through sheath to the radio-frequency discharge period. Results of calculations show that big dust particles slow down ions in rf-sheaths, but the presence small dust particles can increase energy of ions. It is explained by the increasing of the potential drop near electrode. Досліджуються функції розподілу іонів за енергією в приелектродному шарі з пиловими частинками в
ємнісному РЧ-розряді в силані та результати порівнюються з результатами, одержаними в аргоновому розряді.
Моделювання виконувалось за допомогою PIC/MCC методу для широкого діапазону тиску, концентрації та
радіусу пилових частинок. Наша модель включає зіткнення електронів з нейтралами, різні види зіткнень іонів з
нейтралами, зіткнення позитивних та негативних іонів. Результати обчислень показали, що функції розподілу
іонів за енергією для позитивних іонів SiH⁺³ в силановому РЧ-розряді відрізняються від функцій розподілу
іонів в аргоновому розряді. Іони біля електроду одержують більшу енергію в електронегативному розряді
внаслідок несуттєвої ролі процесів обміну зарядом в цих розрядах. В іонних функціях розподілу з’являються
піки, які пов’язані зі значним зменшенням ширини РЧ- приелектродного шару і відношення часу прольоту іонів
через приелектродний шар до періоду розряду Исследуются функции распределения ионов по энергии в приэлектродном слое с пылевыми частицами в
емкостном РЧ-разряде в силане и результаты сравниваются с результатами, полученными в аргоновом разряде.
Моделирование выполнялось при помощи PIC/MCC метода в широком диапазоне давлений, концентраций и
радиусов пылевых частиц. Наша модель включает столкновения электронов с нейтралами, различные виды
столкновений ионов с нейтралами, столкновения позитивных и негативных ионов. Результаты вычислений
показали, что функции распределения ионов по энергии для позитивных ионов SiH⁺³ в силановом РЧ-разряде
отличаются от функций распределения ионов в аргоновом разряде. Ионы вблизи электрода имеют большую
энергию в электроотрицательном газе вследствие несущественной роли процессов перезарядки в этих разрядах.
В ионных функциях распределения появляются пики, которые связаны со значительным уменьшением ширины
РЧ-приэлектродного слоя и отношения времени пересечения ионами приэлектродного слоя к периоду разряда.